Common climatic signal from glaciers in the European Alps over the last 50 years. Issue 3 (13th February 2017) - Vincent, C.; Fischer, A.; Mayer, C.; Bauder, A.; Galos, S. P.; Funk, M.; Thibert, E.; Six, D.; Braun, L.; Huss, M.
Abstract: Conventional glacier‐wide mass balances are commonly used to study the effect of climate forcing on glacier melt. Unfortunately, the glacier‐wide mass balances are also influenced by the glacier's dynamic response. Investigations on the effects of climate forcing on glaciers can be largely improved by analyzing point mass balances. Using a statistical model, we have found that 52% of the year‐to‐year deviations in the point mass balances of six glaciers distributed across the entire European Alps can be attributed to a common variability. Point mass balance changes reveal remarkable regional consistencies reaching 80% for glaciers less than 10 km apart. Compared to the steady state conditions of the 1962–1982 period, the surface mass balance changes are −0.85 m water equivalent (w.e.) a −1 for 1983–2002 and −1.63 m w.e. a −1 for 2003–2013. This indicates a clear and regionally consistent acceleration of mass loss over recent decades over the entire European Alps. Key Points: Point mass balance analysis reveals remarkable regional consistencies over the Alps with a common variance of 52% for glaciers 400 km apart The signal derived from clusters of stakes on glaciers shows a climatic signal that is unbiased by dynamic glacier response We found a clear acceleration of mass loss over the recent decades greater than those based on glacier‐wide mass balances